2015
DOI: 10.1103/physrevlett.115.164501
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Stabilizes Fluid Invasion into Porous Media via Nonlocal, Cooperative Pore Filling

Abstract: We study the impact of the wetting properties on the immiscible displacement of a viscous fluid in disordered porous media. We present a novel pore-scale model that captures wettability and dynamic effects, including the spatiotemporal nonlocality associated with interface readjustments. Our simulations show that increasing the wettability of the invading fluid (the contact angle) promotes cooperative pore filling that stabilizes the invasion, and that this effect is suppressed as the flow rate increases, due … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
246
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(259 citation statements)
references
References 39 publications
13
246
0
Order By: Relevance
“…Specifically, the morphology of the displacement pattern broadens as the invading fluid becomes more wetting to the medium. This observation was confirmed by recent experiments (20) and pore-scale simulations (21), which found that increasing the medium's affinity to the invading fluid makes the invasion pattern more compact at all Ca. However, the complete range of wetting conditions in imbibition is yet to be fully explored, especially in the regime where the invading fluid is strongly wetting to the porous medium.…”
supporting
confidence: 77%
“…Specifically, the morphology of the displacement pattern broadens as the invading fluid becomes more wetting to the medium. This observation was confirmed by recent experiments (20) and pore-scale simulations (21), which found that increasing the medium's affinity to the invading fluid makes the invasion pattern more compact at all Ca. However, the complete range of wetting conditions in imbibition is yet to be fully explored, especially in the regime where the invading fluid is strongly wetting to the porous medium.…”
supporting
confidence: 77%
“…For high disorder ( λ  = 0.82), we reproduce the transition from CF to VF as the rate increases in drainage8 (wetting angle θ  < 90°, θ measured through the defending fluid, see Fig. 1c), and the smoothing (“stabilizing”) effect of increasing θ towards imbibition ( θ  > 90°), reducing trapping1112 (Fig. 2).…”
Section: Resultsmentioning
confidence: 96%
“…Increasing affinity of the invading fluid (from drainage to imbibition, when the invading fluid is more wetting) smoothes the invasion front, even at high, unfavorable M 10. At low rates, increasing wettability leads to a transition between CF and CO, whereas increasing Ca enhances viscous instabilities promoting VF, regardless of wettability1112. We note that the frequent use of the term “(in)stability” to describe the pattern, and the interchange of “stability” with “efficiency” or “compactness”.…”
mentioning
confidence: 99%
“…This is an expected result; indeed in imbibition the invading fingers are expected to be broader [96][97][98], since they have the tendency to wet the pores and thus explore more easily neighboring pores. Figure 17 shows depth saturation profiles for both imbibition and drainage experiments in the viscous fingering regime.…”
Section: Imbibition and Drainage With Imposed Flux (Velocity-inlet Anmentioning
confidence: 91%